Intra-Articular Mineralization on Computerized Tomography of the Knee and Risk of Cartilage Damage: The Multicenter Osteoarthritis Study - Liew, Jean W.; Jarraya, Mohammed; Guermazi, Ali; Lynch, John; Felson, David; Nevitt, Michael; Lewis, Cora E.; Torner, James; Roemer, Frank; Crema, Michel D.; Wang, Na; Becce, Fabio; et al. (Arthritis and Rheumatology, 2024)
Objective: Intra-articular (IA) mineralization may contribute to osteoarthritis (OA) structural progression. We studied the association of IA mineralization on knee computed tomography (CT) with cartilage damage worsening on knee magnetic resonance imaging (MRI), with a focus on location- and tissue-specific effects. Methods: Participants from the Multicenter Osteoarthritis Study with knee CT and MRI scans were included. Presence of IA mineralization on CT was defined as a Boston University Calcium Knee Score >0 anywhere in the knee. Cartilage worsening on MRI was defined as any increase in the MRI OA Knee Score, including incident damage. We evaluated the association of whole-knee, compartment-specific (ie, medial or lateral), and subregion-specific (ie, location-matched) IA mineralization at baseline with cartilage worsening at two years’ follow-up in the corresponding locations using binomial regression with generalized estimating equations, adjusting for age, sex, and body mass index (BMI). Results: We included 1,673 participants (mean age 60 years, 56% female, mean BMI 29). Nine percent had any IA mineralization in the knee, and 47.4% had any cartilage worsening on follow-up. Mineralization of any tissue in the knee, regardless of location, was not associated with MRI cartilage worsening. However, cartilage mineralization was associated with 1.39 (95% confidence interval 1.04–1.88) times higher risk of cartilage worsening in the same compartment, with similar results in subregion-specific analysis. Conclusion: CT-detected IA mineralization in the cartilage was associated with higher risk of MRI cartilage worsening in the same compartment and subregion over two years. These findings suggest potential localized, tissue-specific effects of IA mineralization on cartilage pathology in knee OA.
CRIS-Team Scopus Importer:2024-04-19